2009
DOI: 10.1016/j.jvs.2008.10.064
|View full text |Cite
|
Sign up to set email alerts
|

The phase I multicenter trial (STAPLE-1) of the Aptus Endovascular Repair System: Results at 6 months and 1 year

Abstract: These results of the STAPLE-1 trial document the acute safety and feasibility of the Aptus Endograft and EndoStaples. Early follow-up demonstrates excellent 6-month and 1-year results. A pivotal phase II trial is underway at 25 US centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…Endograft fixation in these studies did not exceed a DF of 40 N, 1,2,10-15 which is significantly inferior to the DF achieved in conventional hand-sewn vascular anastomoses, which ranged from 40 to 150 N. 1,2,14,16,17 The helical EndoStaple (Aptus EndoStapling System, Aptus Endosystems, Sunnyvale, Calif) was designed to improve fixation and sealing for the Aptus Endosystems endograft and is also compatible for use with other commercially available endografts. 18,19 The Aptus EndoStaple is a helical "screw-like" metal alloy, 4.5 mm in length and 3.0 mm in diameter, made of a wire that measures 0.5 mm in diameter. It features a tapered needlepoint that allows penetration through nondiseased and diffusely calcified vascular tissue and prevents overpenetration.…”
mentioning
confidence: 99%
“…Endograft fixation in these studies did not exceed a DF of 40 N, 1,2,10-15 which is significantly inferior to the DF achieved in conventional hand-sewn vascular anastomoses, which ranged from 40 to 150 N. 1,2,14,16,17 The helical EndoStaple (Aptus EndoStapling System, Aptus Endosystems, Sunnyvale, Calif) was designed to improve fixation and sealing for the Aptus Endosystems endograft and is also compatible for use with other commercially available endografts. 18,19 The Aptus EndoStaple is a helical "screw-like" metal alloy, 4.5 mm in length and 3.0 mm in diameter, made of a wire that measures 0.5 mm in diameter. It features a tapered needlepoint that allows penetration through nondiseased and diffusely calcified vascular tissue and prevents overpenetration.…”
mentioning
confidence: 99%
“…The length of the endostaples is 4 mm, and complications like perforation of adjacent structures like the inferior vena cava or bowels have not been described. 7 Bench tests of the use of these endostaples in the AneuRx and Talent endograft did not show type III endoleaks due to graft tears (unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…The endostapling system (Aptus Endosystems, Inc, Sunnyvale, Calif) consists of two complementary devices: a 16-Fr outer diameter deflectable guide sheath and an electronically-controlled stapler device that implants each staple in a two-stage procedure, which allows retraction and repositioning of the staple during deployment. 7 When the top of the endoguide has been positioned at the level of the part of the endograft that has to be fixated, the obturator is removed. The endoguide has a steerable deflecting tip for precise positioning, perpendicular to the graft material.…”
Section: Discussionmentioning
confidence: 99%
“…8 So far, the endostapling concept has been evaluated in a handful of clinical studies. Deaton et al 9 reported a primary technical success rate of 100% within the multicentric STAPLE-1 trial. There were no endostaple-related adverse events, device integrity failures, migrations, or conversions in 14 of the 21 patients, in whom a 12-month follow-up was available.…”
Section: Discussionmentioning
confidence: 99%